Online sexual exploitation of children (Damascus University Journal for legal sciences, 2024)
The survival of the human race depends on the story of creation that charted its course and defined its chapters with the greatest formation of God Almighty, Creator of heaven and earth. Therefore, the children who are the product of this amazing coordination are the mainstay of this survival, and our care for them is one of our most important duties and rights.  In addition, the development of human civilization depends mainly on the upbringing of good generations, raising them and immunizing them with good manners and cohabitation, and arming them with science and culture, which keeps them away from bad path and the stray from the right path.  But humanity, since the beginning of its existence on this planet, has committed many mistakes and violations that are far from our human instinct, prompted by various reasons of greed, desires and so on.  Here is Cain killing his brother Abel ,and humanity is still so far and will continue until the end of time to commit mistakes and transgress taboos.  Therefore, it was incumbent upon each of us to confront these malicious tendencies, starting with committing ourselves to the path of righteousness, and playing the right role in education and raising awareness, and returning those who strayed from the path of righteousness.  From here also, after humanity entered under the umbrella of the social contract, the sponsoring state became represented by its educational, security and judicial bodies, which are directly responsible for controlling and correcting the deviations of the violators behaviour. Accordingly, the legislator resolutely confronted these acts that are out of the controls of morals and law, and it began with children and minors, where humanity first started and gave them priority in protection, and tightened the penalties for violators of their rights, especially what affects the integrity of their bodies. The same applies to all international legislation, especially those related to human rights, of which the rights of the child had a good share.  The Syrian society, including the Syrian legislator, did not deviate from this approach, which gave the child all care and attention. The Syrian legislator tightened the penalties if the victim is under the age of majority, emphasizing the importance of building a strong and healthy generation, and building a society based on solid foundations. The same is applied for the Arab legislature who followed the same example generally.
Keywords: Sexual Exploitation; Online